Waveform-adaptive large-dynamic high-precision time measuring instrument and measuring method - WU TENG; CHEN ZIYANG; GUO HONG (2022)
The invention discloses a waveform-adaptive large-dynamic high-precision time measuring instrument and a measuring method. The frequency meter is used for roughly measuring the pulse period; performing calculation processing according to a measurement result of the frequency meter to obtain four parameters, namely pulse filtering quantity and cavity length tuning quantity of the three mode-locked lasers respectively; dynamic filtering and cavity length stretching are realized through a controller; carrying out pairwise beat frequency on the three mode-locked lasers to obtain two paths of beat frequency signals; the final time difference information is obtained through the collection and data processing of the beat frequency signal. The method has the advantages of high adaptability, large dynamic range, high measurement precision and the like. 本发明公开了一种波形自适应的大动态高精度时间测量仪器及测量方法。本发明利用频率计进行脉冲周期的粗略测定；根据频率计的测量结果进行计算处理，获得脉冲滤波量、三个锁模激光器分别的腔长调谐量共四个参数；通过控制器实现动态滤波、腔长拉伸；随后对三台锁模激光器进行两两拍频，获得两路拍频信号；通过对拍频信号进行采集、数据处理得到最终时间差信息。本